Electronic clock, azan reader, and ringer (digital clock) / Mohd Khairil Adzhar Mahmood and Mohd Nirwan Aliasa’a - Mahmood, Mohd Khairil Adzhar; Aliasa’a, Mohd Nirwan (2005)
Digital clock azan reader is a device designed to display the actual time of that seconds. It also is an alarm device to give the users an alert or signal of what they have to do on that time of the clock is being set by the user itself. However, all the products on the market do have some disadvantages. As we all know that almost all of electronics gadgets manufacturer like Taiwan and China is a non - Muslims country. So, it would be very difficult for us in Malaysia for example to find all the products that have a religious symbolic such as azan reader. That is why we have decided to create an azan reader with digital clock. The proposed project will provide a more reliable and accurate device for Muslims in our country for example. This project will benefit all of us by giving correct and accurate time. It also can give us alert on certain time of time we wants to. We think that this product can be operated at all places and at all times. Users can operate it without any problems as it is user friendly.